(untitled) (Research, Society and Development, 2024)
Neonatal palliative care is a recent topic in Brazil and there is still little national literature available. Thus, the study aimed to describe the profile of newborns who died between January 2022 and December 2023, enumerate how many received palliative care and compare those who died in the NICU and in the delivery room. Data were obtained through review of death certificates and medical records and the statistical analysis performed was based on a variety of methods, including descriptive measures and hypothesis testing. 51 deaths were found, with a median weight of 775 g and a median GA of 25 weeks. Extremely premature babies, live births in the abortion range corresponded to 19.6% of the sample. Lifespan was up to 24 hours in 61% of cases. The main final causes of death (52.8%) are related to respiratory distress syndrome, prematurity and asphyxia. The institution has a palliative care protocol, with the majority of patients (71%) not being resuscitated at the time of death, but rather being offered palliative care. Of those who received palliatives, 42% had a written end-of-life care plan. When comparing deaths in the delivery room with those in the NICU, we identified a lower gestation rate and weight, where 44% were below the viability zone, which is 22 weeks. Deaths in the NICU had more end-of-life plans, due to the longer time for the palliative team to work.